THE ONSET OF CLINICAL MANIFESTATIONS IN INFLAMMATORY BOWEL DISEASE PATIENTS - NÓBREGA,Viviane Gomes (2018)
ABSTRACT BACKGROUND: The diagnosis of inflammatory bowel disease is often delayed because of the lack of an ability to recognize its major clinical manifestations. OBJECTIVE: Our study aimed to describe the onset of clinical manifestations in inflammatory bowel disease patients. METHODS: A cross-sectional study. Investigators obtained data from interviews and the medical records of inflammatory bowel disease patients from a reference centre located in Brazil. RESULTS: A total of 306 patients were included. The mean time between onset of symptoms and diagnosis was 28 months for Crohn’s disease and 19 months for ulcerative colitis. The main clinical manifestations in Crohn’s disease patients were weight loss, abdominal pain, diarrhoea and asthenia. The most relevant symptoms in ulcerative colitis patients were blood in the stool, faecal urgency, diarrhoea, mucus in the stool, weight loss, abdominal pain and asthenia. It was observed that weight loss, abdominal pain and distension, asthenia, appetite loss, anaemia, insomnia, fever, nausea, perianal disease, extraintestinal manifestation, oral thrush, vomiting and abdominal mass were more frequent in Crohn’s patients than in ulcerative colitis patients. The frequencies of urgency, faecal incontinence, faeces with mucus and blood, tenesmus and constipation were higher in ulcerative colitis patients than in Crohn’s disease patients. The mean time from the onset of clinical symptoms to the diagnosis of Crohn’s disease was 37 months for patients with ileocolonic location, 26 months for patients with ileum location and 18 months for patients with colon location. In ulcerative colitis patients, the mean time from the onset of symptoms to diagnosis was 52 months for proctitis, 12 months for left-sided colitis and 12 months for extensive colitis. CONCLUSION: Ulcerative colitis presented a high frequency of intestinal symptoms, and Crohn’s disease showed a high frequency of systemic manifestations at the onset of manifestation. There was a long delay in diagnosis, but individuals with more extensive disease and more obvious symptoms showed a shorter delay.